(3GdMhGTj GdCRgQjI aj Md CdaGX GdebOeI GdLRQjIs - (3GdLQLGhj GdCRgQj GdeUQj, Rjf GdOjf, GdhbGO, NGdO Hf YHO Gddg Hf CHj HcQ, J (B905 (3g`s ((3EHQGgje OGhO Hf OGhOs)
(3ChdgG (B:s
(3HYO GdHSedI ; jbhd NGdO Hf YHO Gddg GdCRgQj GdMeO ddg GdPj GfRd Ydi YHOg GdcJGH CeG HYO aEf ef Chd eG JUQa ajg Gdgee GdYhGd cdGe Gddg GdcHjQ GdeJYGd hCge eG ojHJOC Hg JLhjO MQhag hef CfaY eG QCjJ aj gPG GdTCf GQLhR TjN GdESdGe GHf GdLRQj LeYJ MhGT hSejJgG GdMhGTj GdCRgQjIs
(3BNQgG (B:s
(3T GdJbVj GdGfJgGA TjFG aTjFG hGdfXe LeY GdCTjGA Ydi gjTI eJfGSHI hbhdg JbOeg Edi JMaI hgOjI hNJegG HGdMeO hGdUdGI dJchf ejehfI GdGaJJGM hGdGNJJGes
(3efbhdg ef fSNI GdeDda GdeDQNI (B: 867 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2 / 297s
(3eYLe GdeDdajf (B1 / 668s
(3cTa GdXfhf (B2 / 1800s
(3TPQGJ GdPgH (B8 / 26s
Keywords: (3GdbQGAGJ hGdJLhjOs